International cooperation and distance education: An experience in Bahia / Brazil (Revista Contexto & Educação, 2025)
This article addresses the teaching and student experience in the Specialization Course in Open and Digital Technologies and Education, offered by University of Recôncavo da Bahia, in partnership with Open University of Portugal. By discussing and deepening the debate on the importance of mechanisms for international cooperation agreements in education and the relevance of the use of technologies in Education, it exposes possibilities for the development of scientific production, teacher training and institutional transformation within a scenario of internationalization of education. The writing was transversalized by results obtained from the literature review, documentary research and field research, in which the narratives represent the knowledge of reality based on the subjectivity of the participants. In this aspect, the expansion of scientific and technological dialogue and the socialization of knowledge were materialized through publications arising from course completion work.
Keywords: cooperation agreement; distance education; internationalization; technologies